The A STUDY ON THE PLAYS OF GIRISH KARNAD AND VARIOUS SYMBOLS USED IN HIS PLAYS - Dinesh Kumar Sharma , Japneet Kaur (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Girish Raghunath Karnad is regarded as one of the best dramatists in Indo Anglian literature, and is known for his adaptability. He is a cultural administrator, translator, critic, director, actor, poet, and dramatist, among other things. Karnad has received widespread appreciation for his complex portrayal of topics in his plays, which examine existential issues and the human condition. Karnad's use of a variety of dramatic devices adds to the innovative merging of Indian reason with western emotive culture in his plays. A careful examination of Karnad's emotional devices in his major plays reveals the playwright's elegant realism and inventiveness, and allows the reader to derive new meanings from the texts.